INVESTIGATING THE INFLUENCE OF INTERDISCIPLINARY TEAMWORK AND PROFESSIONAL DEVELOPMENT ON PATIENT OUTCOMES AND JOB SATISFACTION AMONG NURSES, HEALTH ADMINISTRATORS, AND EMERGENCY MEDICAL SERVICE TECHNICIANS IN SAUDI ARABIA - Maryam Khalaf Essa Alanazi, Amirah Eidan Alshammari, Turkiah Khalaf Essa Alanazi, Jawaher Dali Hudayris Alshammari, Nawaf Ibraheem F Almutairi, Fakhri Ibraheem F Almutairi, Naiyf Ibraheem F Almutairi, Bader Kamyan Basheer Alanazi (Chelonian Research Foundation, 2022)
Interdisciplinary teamwork and professional development are crucial factors in ensuring high-quality patient care and job satisfaction among healthcare professionals. This study aimed to investigate the influence of interdisciplinary teamwork and professional development on patient outcomes and job satisfaction among nurses, health administrators, and emergency medical service technicians in Saudi Arabia. A mixed-methods approach was employed, including a cross-sectional survey of 750 healthcare professionals, a retrospective analysis of 1,500 patient records, and semi-structured interviews with 30 healthcare professionals. The results revealed that interdisciplinary teamwork and professional development were significantly associated with improved patient outcomes, such as reduced medication errors (β = -0.28, p < 0.001), decreased patient falls (β = -0.22, p < 0.01), and shorter hospital stays (β = -0.19, p < 0.01). Moreover, healthcare professionals who reported higher levels of interdisciplinary teamwork and professional development exhibited greater job satisfaction (β = 0.35, p < 0.001). The qualitative findings highlighted the importance of effective communication, mutual respect, and continuous learning in fostering interdisciplinary collaboration and professional growth. The study underscores the need for healthcare organizations in Saudi Arabia to prioritize initiatives that promote interdisciplinary teamwork and professional development to enhance patient outcomes and job satisfaction among healthcare professionals. Keywords: interdisciplinary teamwork, professional development, patient outcomes, job satisfaction, nurses, health administrators, emergency medical service technicians, Saudi Arabia